A systematic review and meta-regression analysis of prophylactic gabapentin for postoperative pain - Doleman, Brett; Heinink, T.P.; Faleiro, R.J.; Lund, Jonathan N.; Williams, John P. (Wiley, 2015)
We searched MEDLINE, Embase, CINAHL, AMED and CENTRAL databases until December 2014 and included 133 randomised controlled trials of peri-operative gabapentin vs placebo. Gabapentin reduced mean (95% CI) 24-h morphine-equivalent consumption by 8.44 (7.26–9.62) mg, p < 0.001, whereas more specific reductions in morphine equivalents were predicted (R2 = 90%, p < 0.001) by the meta-regression equation: 3.73 + (−0.378 × control morphine consumption (mg)) + (−0.0023 × gabapentin dose (mg)) + (−1.917 × anaesthetic type), where ‘anaesthetic type’ is ‘1’ for general anaesthesia and ‘0’ for spinal anaesthesia. The type of surgery was not independently associated with gabapentin effect. Gabapentin reduced postoperative pain scores on a 10-point scale at 1 h, 2 h, 6 h, 12 h and 24 h by a mean (95% CI) of: 1.68 (1.35–2.01); 1.21 (0.88–1.55); 1.28 (0.98–1.57); 1.12 (0.91–1.33); and 0.71 (0.56–0.87), respectively, p < 0.001 for all. The risk ratios (95% CI) for postoperative nausea, vomiting, pruritus and sedation with gabapentin were: 0.78 (0.69–0.87), 0.67 (0.59–0.76), 0.64 (0.51–0.80) and 1.18 (1.09–1.28), respectively, p < 0.001 for all. Gabapentin reduced pre-operative anxiety and increased patient satisfaction on a 10-point scale by a mean (95% CI) of 1.52 (0.78–2.26) points and 0.89 (0.22–1.57) points, p < 0.001 and p = 0.01, respectively. All the effects of gabapentin may have been overestimated by statistically significant small study effects.